O Zagadnieniu Rozprzestrzeniania się Fal Naprężenia w Plastycznym Ośrodku Zawierającym Sztywną Płytę na Granicy Warstw - Podolak, K. (Engineering Transactions, 1974)
The problem of interaction of a plane stress wave with a rigid plate placed between the plastic layer and semi-space which are characterized by different unloading laws is studied. At outer surface of the layer a suddenly increasing pressure (which then monotonically decreases to zero) is given. The solution of the problem is obtained in the form of an infinite series which converges uniformly. Using an electronic computer, some numerical results are obtained. They give us interesting information concerning the dynamic behaviour of the plate.